Guanxi beliefs, self-efficacy beliefs, and depressive symptoms—Analysis of the effects of Chinese-style special relationships - Li, Guoqing; Ha, Buerzhasala; Zhang, Jie (Frontiers in Psychology, 2025)
IntroductionDepression is a significant global health concern, with a rising number of individuals affected annually. This study examines the influence of cultural and psychological factors on depression within China's collectivist culture, focusing on guanxi beliefs (as an external locus of control), self-efficacy beliefs (as an internal locus of control), and the mediating role of hope.MethodsUsing data from the 2018 China Family Panel Studies (CFPS), multivariate linear regression analysis was conducted to explore the relationships between guanxi beliefs, self-efficacy beliefs, hope, and depressive symptoms. The sample included 29,225 adults aged 18 and above. Depressive symptoms were measured using an 8-item CES-D scale, while guanxi and self-efficacy beliefs were assessed through Likert-scale questions.ResultsStronger *guanxi* beliefs were associated with increased depressive symptoms (β = 0.206, p < 0.001), while stronger self-efficacy beliefs were linked to reduced symptoms (β = −0.151, p < 0.001). Hope mediated these relationships, with guanxi beliefs reducing hope (β = −0.0129, p < 0.01) and self-efficacy enhancing it (β = 0.0867, p < 0.001).DiscussionThe findings highlight the distinct roles of cultural (guanxi) and psychological (self-efficacy) factors in mental health outcomes. Interventions fostering self-efficacy and hope may mitigate depressive symptoms, particularly in cultures where external factors like guanxi are prominent. Future research should explore longitudinal and cross-cultural comparisons to generalize these findings.